The future of microfinance - Lieberman, Ira W.; DiLeo, Paul; Watkins, Todd A.; Kanze, Anna (Brookings Institution Press, 2020)
"This book is based on the results of a workshop at Lehigh University among thirty-four leaders in the industry. The editors, working with contributions from more than a dozen leading authorities in the field, tell the important story of how microfinance developed, how it has met the needs of hundreds of millions of people, and they address key questions about how it can continue to meet those needs in the future"--